The Safety and Efficacy of the Modified Single Incision Non-thoracoscopic Nuss Procedure for Children With Pectus Excavatum - Song, Jishuo; Wang, Quan; Pan, Zhengxia; Wu, Chun; Li, Yonggang; Wang, Gang; Dai, Jiangtao; Xi, Linyun; Li, Hongbo (Frontiers in Pediatrics, 2022)
Background This study described and evaluated the safety and efficacy of a modified single incision non-thoracoscopic Nuss procedure in pectus excavatum (PE) children. Methods PE patients undergoing the non-thoracoscopic Nuss procedure at the Children's Hospital of Chongqing Medical University between January 2017 and December 2020 were retrospectively enrolled. The patients were divided into two groups according to operation procedures: the double incision Nuss (DN) group and the modified single incision Nuss (SN) group. Propensity score matching (PSM) was applied before evaluation of operative and postoperative characteristics to reduce selection bias. Results Of the 502 patients included, 261 were enrolled in the DN group, and 241 in the SN group. The operation time [35.0 (30.0–40.0) vs. 50.0 (40.0–55.0) minutes, P < 0.001] and postoperative inpatient stay [7.0 (6.0–8.0) vs. 7.0 (7.0–8.0) days, P < 0.001] of the patients in the SN group after PSM were significantly shorter than those of the patients in the DN group after PSM. Moreover, median blood loss was significantly less in the SN group after PSM than that in the DN group after PSM [2.0 (1.0–5.0) vs. 5.0 (2.0–5.0) ml, P < 0.001]. There were no significant differences in the incidence of complications between the two groups (P > 0.05). Bar removal was performed in 85 patients in the SN group within 24–42 months after surgery. Additionally, the SN group patients had a significantly lower Haller index (HI) after bar removal [2.36 (2.15–2.55) vs. 3.76 (3.18–4.26), P < 0.001] compared to the initial HI. Conclusions The modified procedure is safe and effective for children with PE and is worthy of clinical application.